Kualitas Layanan Informasi Di Kantor Pusat Informasi Pengembangan Permukiman Dan Bangunan (PIP2B) Provinsi Kalimantan Tengah - Mambang Mambang; Ratna Indah Setyowati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The Residential and Building Development Information Center (PIP2B) is an innovative institution that is targeted to become a public institution that supports the implementation of housing and settlements. Which in its establishment is facilitated by the Central Government and belongs to the Provincial Public Works Department of Central Kalimantan. In support of housing and settlement operations, the Settlement and Building Development Information Center (PIP2B) provides ease of services and access to information on various elements: planners, implementers, building materials entrepreneurs, government, communities and academics. This research is motivated by the many complaints from Palangka Raya City community about Information Service in Information Center of Settlement and Building Development (PIP2B) still can not be felt by society evenly. Type of research used is descriptive qualitative research. Research that aims to describe and describe events and phenomena that occur in the field and presents data in a systematic, factual, and accurate about the facts or phenomena that occur in the field. Data collection techniques in this study using observation techniques, interviews, and documentation. The results showed that based on the results of interviews and research documentation with Tangible indicator, realibility, Responsiveness, Assurance and Empathy as well as related to service indicators, it can be drawn some conclusions as seen from the many research findings in the field either due to inadequate facilities and infrastructure the lack of facilities provided, and the lack of communication between the Office of Information Development Information Settlement and Building (PIP2B) with the Ministry of PUPR.